Pengaruh Beban Kerja Dan Lingkungan Kerja Terhadap Kinerja Karyawan Pada PT. Lancs Arche Consumma Jakarta - Muhamad Firdaus; Sofyan Marwansyah (Jurnal Inovasi Bisnis Manajemen dan Akuntansi, 2025)
Excessive workload can lead to physical and mental fatigue, while an uncomfortable work environment can reduce productivity. In fact, Minister of Manpower Regulation No. 5 of 2018 and Law No. 13 of 2003 regulate working hour limits and emphasize the importance of creating a safe and healthy work environment. This study aims to determine the influence of workload and work environment on employee performance, both partially and simultaneously. The research method used is quantitative with a saturated sampling technique, involving the entire population of 40 employees. Data were collected through questionnaires and analyzed using data quality tests, classical assumption tests, hypothesis testing, and the coefficient of determination. The results show that workload has no partial effect on employee performance. However, the work environment has a partial effect. Simultaneously, workload and work environment have a significant effect on employee performance. These findings indicate that the combination of workload and work environment plays a crucial role in improving performance. Therefore, companies need to pay close attention to workload distribution and create a supportive work environment to ensure that organizational goals are achieved effectively and efficiently.